2017
DOI: 10.4274/tjod.57984
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tubal torsion: Successful preoperative diagnosis of five cases using ultrasound and management with laparoscopy

Abstract: Our aim was to evaluate the presentation and diagnostic evaluation of patients with isolated tubal torsion and to evaluate the surgical approach to these patients. We also aimed to define the ultrasonographic diagnostic criteria. Five patients with isolated tubal torsion who were admitted to our gynecology department between January 2014 and January 2017 were evaluated and included in this study. All cases were diagnosed through ultrasonographic imaging alone. The preoperative findings of the patients were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…[ 10 ] Color Doppler may be useful in diagnosing the IFTT, but normal flow definitely will not rule out the torsion. A whirlpool sign is known for its high sensitivity in diagnosing the IFTT,[ 9 11 ] which was not assessed in our study; hence, the diagnosis could be missed and none of the patients were identified as adnexal torsion by imaging modality in our series.…”
Section: Discussionmentioning
confidence: 89%
“…[ 10 ] Color Doppler may be useful in diagnosing the IFTT, but normal flow definitely will not rule out the torsion. A whirlpool sign is known for its high sensitivity in diagnosing the IFTT,[ 9 11 ] which was not assessed in our study; hence, the diagnosis could be missed and none of the patients were identified as adnexal torsion by imaging modality in our series.…”
Section: Discussionmentioning
confidence: 89%
“…Although normal vascular flow is observed in the ovaries, a lack of diastolic flow or an observation of diastolic reverse stream together with high-impedance arterial stream in Doppler US of the adnexal mass wall may increase the suspicion of tubal torsion. However, the observation of a normal stream form by Doppler US does not always exclude the torsion [ 1 , 11 , 17 , 18 ]. In our patient’s case, tubal pathology was suspected because of the normal appearance of the ovaries separately and detection of an irregular cystic mass in the adnexal region by US, and tubal torsion was also considered among the preoperative differential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Although imaging methods are generally helpful in patients with acute abdominal pain, fallopian tube torsion is rarely diagnosed preoperatively [ 13 ]. However, Fadıloğlu et al reported that five patients with lower abdominal pain of different severities were diagnosed with preoperative tubal torsion using US alone; no other imaging method other than US was used, and these diagnoses were confirmed by laparoscopy [ 17 ]. In our opinion, especially in women with acute abdominal pain who are of reproductive age, tubal torsion can be seriously suspected by physical examination and US evaluation if considered among the differential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Given visualisation of this sign will provide a definitive diagnosis of this challenging condition, careful scanning of the adnexa by the sonographer is warranted. It has been suggested that the correct evaluation of the adnexa commences at the interstitial tubal segment and extends towards the fimbria . In this case, the whirlpool sign could not be visualised on retrospective analysis of stored longitudinal and transverse cine loops of the right adnexa, even after reviewing the operative findings.…”
Section: Discussionmentioning
confidence: 99%